High-strength multifunctional glass panel and processing technology thereof
Through the innovative design of high alumina silicate glass substrate, surface composite functional layer and embedded conductive-insulating composite layer, the problems of high energy consumption and complex process are solved, and the coordinated optimization of the mechanical properties and functional characteristics of high-strength multifunctional glass panels is achieved, which improves bending strength and reduces thermal conductivity, and meets the needs of smart homes and green buildings.
Patent Information
- Application Number
- CN202510931000.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-08-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-strength multifunctional glass panels have high energy consumption, complex process, poor compatibility of functional layer interfaces, and insufficient coordinated optimization of mechanical properties and functional characteristics, resulting in insufficient strength, functional fragmentation, and weak environmental adaptability in smart homes and energy-saving buildings.
The structural design of high alumina silicate glass substrate, surface composite functional layer and embedded conductive-heat insulation composite layer is adopted. Through the integration of the bionic honeycomb microstructure layer and the ternary nanocomposite coating layer, combined with a low-temperature one-step process, the integration of stress dispersion, anti-reflection, hydrophobic and antibacterial functions is achieved, and the silver nanowire-aerogel composite grid is embedded to achieve the coordination between conductivity and heat insulation.
The bending strength of glass panels is improved to 150-180MPa, the thermal conductivity is reduced to 0.03W/m·K, and the production process is simplified to meet the high-strength, multi-functional and low-cost needs of smart homes and green buildings.
Smart Images

Figure CN120518330A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass panels, and in particular to a high-strength multifunctional glass panel and a processing technology thereof. Background Art
[0002] Currently, the mainstream technology for high-strength, multifunctional glass panels relies on chemical strengthening (such as K⁺ ion exchange in soda-lime glass) and physical tempering (such as hot air quenching) to enhance mechanical properties, while expanding functionality through multi-step coating or lamination processes. For example, smartphone cover glass typically utilizes an aluminosilicate substrate that undergoes ion exchange to form a surface compressive stress layer (flexural strength 300-500 MPa), followed by magnetron sputtering to deposit an ITO conductive layer and an AF oleophobic coating. In the architectural and home furnishing sectors, lamination processes (such as PVB / EVA interlayers) are used to achieve safety and explosion protection or embed LED light-guiding structures. Furthermore, to meet requirements for thermal insulation and antibacterial properties, existing technologies typically layer titanium dioxide photocatalytic layers and low-emissivity (Low-E) films on the glass surface in stages.
[0003] However, these technologies have significant limitations: First, chemical strengthening relies on high-temperature molten salt treatment (400-450°C), which consumes a lot of energy and produces nitrate-containing wastewater, placing significant environmental pressure. Second, the stacking of functional layers leads to poor interface compatibility. For example, the high thermal conductivity of the ITO conductive layer (~10W / m·K) conflicts with the need for thermal insulation, making it difficult to coordinate touch and insulation functions. Third, multi-layer coatings require multiple deposition and curing steps (e.g., separate processing steps for the anti-reflective layer, hydrophobic layer, and antibacterial layer), resulting in complex processes and escalating costs. More critically, traditional structural designs rely too heavily on the modification of a single functional layer and lack the coordinated optimization of mechanical properties and functional characteristics. This results in glass panels facing bottlenecks such as insufficient strength, fragmented functionality, and poor environmental adaptability in scenarios such as smart homes and energy-saving buildings. Summary of the Invention
[0004] The main purpose of the present invention is to provide a high-strength multifunctional glass panel and its processing technology, aiming to reduce production energy consumption and achieve multifunctional integration through structural innovation, breaking through the technical bottleneck of traditional glass panels in the coordination of mechanical properties and functions.
[0005] To achieve the above object, the present invention proposes a high-strength multifunctional glass panel, comprising a high-aluminum silicate glass substrate, a surface composite functional layer, and an embedded conductive-heat-insulating composite layer; The Al2O3 content in the high aluminosilicate glass substrate is 15-20wt%, and the thickness of the high aluminosilicate glass substrate is 2-6mm; The surface composite functional layer includes a microstructure layer and a SiO2-TiO2-ZnO ternary nanocomposite coating layer from the inside to the outside, wherein the microstructure layer has a honeycomb structure, the inner wall of the microstructure layer is covered with a hydrophobic coating, and the thickness of the SiO2-TiO2-ZnO ternary nanocomposite coating layer is 50-200 nm; The embedded conductive-thermal insulation composite layer is located inside the high-alumina silicate glass substrate. The embedded conductive-thermal insulation composite layer is composed of a silver nanowire grid and silica aerogel filling the grid gaps. The silver nanowire grid is composed of a plurality of silver nanowires. The silver nanowire width is ≤20μm, and the grid spacing of the silver nanowire grid is 1-3mm.
[0006] In a possible implementation, the hydrophobic coating of the microstructure layer is a fluorosilane compound, and the thickness of the microstructure layer is 10-30 nm.
[0007] In a possible embodiment, the molar ratio of SiO2, TiO2, and ZnO in the SiO2-TiO2-ZnO ternary nanocomposite coating layer is (5-7): (2-4):1.
[0008] In one possible embodiment, the silica aerogel has a pore size of 10-50 nm and a density of 0.05-0.15 g / cm 3 .
[0009] A process for processing a high-strength multifunctional glass panel as described above comprises the following steps: S1, substrate forming and pretreatment, using a float process to prepare a high-alumina silicate glass substrate with an Al2O3 content of 15-20wt%, and then plasma cleaning after cutting; S2. Microstructure processing: Using UV nanoimprint technology, a honeycomb microstructure with a unit size of 10-50 μm and a depth of 5-20 μm is imprinted on the substrate surface. The imprinting conditions are: pressure 3-8 MPa, temperature 150-200 ° C, UV curing wavelength 365 nm, intensity 40-60 mW / cm 2 ; S3, preparation of embedded conductive-insulating composite layer, depositing silver nanowire grid with line width ≤ 20μm on the substrate surface by inkjet printing, followed by vacuum injection of silica aerogel precursor, and heating and curing at 80-100℃ to form aerogel filling layer; S4, multifunctional composite coating, immersing the substrate in SiO2-TiO2-ZnO sol at a pulling speed of 1-3 mm / s, and forming a ternary nanocomposite coating layer by ultraviolet curing, wherein the molar ratio of SiO2, TiO2, and ZnO in the sol is (5-7): (2-4): 1; S5, lamination and strengthening, laminating the coated substrate and another glass substrate with the EVA film, placing them in an autoclave at a pressure of 1.0-1.5 MPa and a temperature of 120-140° C. for 0.5-1.5 hours.
[0010] In a possible embodiment, the mold of the UV nanoimprinting technology in step S2 is a nickel-based honeycomb structure template, the surface of which is coated with a release agent, and the release agent is a perfluoropolyether compound.
[0011] In a possible implementation, the deposition accuracy of the silver nanowire grid in step S3 is ±2 μm, and the aerogel precursor is methyltrimethoxysilane hydrolyzate.
[0012] In one possible embodiment, the UV curing conditions in step S4 are: wavelength 365nm, intensity 50-80mW / cm 2 , time is 5 to 15 minutes.
[0013] The working principle and beneficial effects of the present invention are: The technical solution of the present invention achieves a one-step integration of stress dispersion and anti-reflection / hydrophobic / antibacterial functions by constructing a bionic honeycomb microstructure layer on the surface of the glass panel and simultaneously depositing a ternary nanocomposite coating layer, reducing dependence on traditional ion exchange processes and solving the problems of high energy consumption and multiple coating processes; by embedding a silver nanowire-aerogel composite grid inside a high-aluminum silicate substrate, physical decoupling of conductivity and thermal insulation is achieved, solving the functional separation problem of the traditional ITO conductive layer's high thermal conductivity and the conflicting insulation requirements; ultimately, through the coordinated design of the structure-functional layer and a low-temperature one-step process, the flexural strength is increased to 150-180 MPa and the thermal conductivity is reduced to below 0.03 W / m·K, while simplifying the production process, meeting the comprehensive requirements of smart homes and green buildings for high-strength, multi-functional, and low-cost glass panels. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0015] Figure 1 It is a process flow chart of the present invention.
[0016] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings and in conjunction with the embodiments. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of this application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application. Example 1
[0018] Example 1 proposes a high-strength multifunctional glass panel, including a high-aluminum silicate glass substrate, a surface composite functional layer, and an embedded conductive-heat-insulating composite layer.
[0019] The Al2O3 content in the high aluminosilicate glass substrate is 15-20wt%, and the thickness of the high aluminosilicate glass substrate is 2-6mm.
[0020] High-aluminosilicate glass substrates serve as the mechanical support core of glass panels, providing fundamental strength and heat resistance. A 15-20wt% Al₂O₃ content enhances the density of the glass network, significantly increasing the flexural strength of the glass substrate compared to conventional soda-lime glass (from 70-100 MPa to 150-180 MPa) while maintaining workability (melting temperature ≤ 1700°C). Al₂O₃ content below 15wt% results in insufficient hardness (Mohs hardness < 6) and easy scratching. Al₂O₃ content above 20wt% results in excessively high melting temperatures (>1750°C), increasing energy consumption and production complexity. High-aluminosilicate glass substrates with a thickness of 2-6mm offer a balance between strength and lightweight requirements. Substrates below 2mm in thickness suffer from insufficient impact resistance. Substrates above 6mm in thickness suffer from reduced light transmittance (<85%) and an increase in weight by over 30%.
[0021] The surface composite functional layer includes a microstructure layer and a SiO2-TiO2-ZnO ternary nanocomposite coating layer from the inside to the outside. The microstructure layer has a honeycomb structure. The inner wall of the microstructure layer is covered with a hydrophobic coating. The thickness of the SiO2-TiO2-ZnO ternary nanocomposite coating layer is 50-200nm.
[0022] The surface composite functional layer synergistically enhances mechanical properties and environmental adaptability through the microstructure layer and the SiO2-TiO2-ZnO ternary nanocomposite coating. The bionic honeycomb structure of the microstructure layer effectively disperses stress, increasing bending strength by 30% to 50% (compared to flat glass), while also providing anchor points for the hydrophobic coating. The hydrophobic coating is used to reduce fingerprint adhesion and enhance self-cleaning properties. The SiO2-TiO2-ZnO ternary nanocomposite coating exhibits anti-reflective, super-hydrophobic, and antibacterial properties. The SiO2-TiO2-ZnO ternary nanocomposite coating, with a thickness of 50-200nm, ensures film continuity, prevents cracking caused by internal stress, and maintains reflectivity below 2%. If the thickness of the SiO2-TiO2-ZnO ternary nanocomposite coating layer is less than 50nm, the film layer will easily become discontinuous and the function will fail; if the thickness of the SiO2-TiO2-ZnO ternary nanocomposite coating layer is less than 200nm, cracks will occur due to internal stress, and the reflectivity will rise back to more than 5%.
[0023] The embedded conductive-thermal insulation composite layer is located inside the high-alumina silicate glass substrate. The embedded conductive-thermal insulation composite layer is composed of a silver nanowire grid and silica aerogel filling the grid gaps. The silver nanowire grid is composed of a number of silver nanowires with a line width of ≤20μm and a grid spacing of 1-3mm.
[0024] Embedded conductive-insulating composite layers achieve physical synergy between conductivity and insulation, resolving conflicts in traditional functional layers. Silver nanowire grids, formed by meshing silver nanowires to form conductive pathways, replace traditional ITO coatings and support smart features such as touchscreens and wireless charging. Their grid design balances conductivity and light transmittance, avoiding light blockage by large metal layers. A silver nanowire grid with a wire width of 20μm or less effectively improves transparency. Widths greater than 20μm make the grid lines visible, impacting the usability and transparency of the glass panel. A silver nanowire grid with a spacing of 1-3mm reduces light scattering and balances conductive uniformity with optical interference (moiré suppression). A mesh spacing greater than 3mm degrades conductive uniformity, impacting panel usability. A mesh spacing less than 1mm significantly increases silver nanowire usage, increasing costs and reducing light transmittance. Silica aerogel utilizes its nanoporous structure to block heat conduction, reducing the overall thermal conductivity of the glass and preventing heat loss or the introduction of high temperatures.
[0025] In this embodiment, the hydrophobic coating of the microstructure layer is a fluorosilane compound, and the thickness of the microstructure layer is 10-30 nm.
[0026] The low surface energy of fluorosilane creates a water contact angle ≥110°, creating a lotus effect that reduces the adhesion of contaminants such as water stains and fingerprints, and enhances the self-cleaning ability of the glass surface. A microstructured layer with a thickness of 10-30nm ensures complete coverage of the microstructure's inner walls, preventing exposed areas that could lead to hydrophobic failure. It also forms a stable chemical bond, enhancing wear resistance. The hydrophobic coating covers the inner walls of the honeycomb microstructure, guiding droplets to roll off quickly through a capillary effect.
[0027] In this embodiment, the molar ratio of SiO2, TiO2, and ZnO in the SiO2-TiO2-ZnO ternary nanocomposite coating layer is (5-7): (2-4): 1.
[0028] 5-7mol% SiO2 can provide an anti-reflection skeleton, reduce the reflectivity to ≤2%, and make the transmittance >92%. At the same time, high content of SiO2 can enhance the mechanical strength of the coating. 2-4mol% TiO2 can effectively release Zn 2+ ions, destroying microbial cell membranes, with a 24-hour antibacterial rate of >99%. The molar ratio of SiO2, TiO2, and ZnO is preferably 5:3:1, which achieves optimal overall performance. Specifically, it can achieve a reflectivity of 1.5%, an antibacterial rate of 99.2%, and a light transmittance of 93%.
[0029] In this embodiment, the pore size of the silica aerogel is 10-50 nm and the density is 0.05-0.15 g / cm 3 .
[0030] Silica aerogel with a pore size of 10-50nm has nanoscale pores that can effectively inhibit the free path of gas molecules and block convective heat transfer. If the pore size is greater than 50nm, the proportion of convective conduction will be too large, and the thermal conductivity will increase; if the pore size is less than 10nm, the difficulty of preparation will be greatly increased, resulting in increased costs. Silica aerogel with a density of 0.05-0.15g / cm3 can ensure high porosity and achieve optimal thermal insulation performance. If the density is less than 0.05g / cm3, the nanoporous network skeleton of the aerogel is too sparse, and the porosity exceeds 98%, resulting in a significant decrease in the mechanical strength of the material; if the density is greater than 0.15g / cm3, the porosity will be less than 85%, resulting in a significant decrease in thermal insulation capacity. Example 2
[0031] like Figure 1 As shown, Example 2 proposes a processing process for a high-strength multifunctional glass panel as described above, comprising the following steps: S1. Substrate forming and pretreatment: A high-alumina silicate glass substrate with an Al2O3 content of 15-20wt% is prepared by a float process, and then plasma cleaning is performed after cutting.
[0032] The float process can reduce energy consumption during the preparation process. Plasma cleaning can replace hydrofluoric acid chemical cleaning. It does not cause waste liquid pollution, which can improve surface cleanliness and enhance the adhesion of subsequent coatings.
[0033] S2. Microstructure processing: Using UV nanoimprint technology, a honeycomb microstructure with a unit size of 10-50 μm and a depth of 5-20 μm is imprinted on the substrate surface. The imprinting conditions are: pressure 3-8 MPa, temperature 150-200 ° C, UV curing wavelength 365 nm, intensity 40-60 mW / cm 2 .
[0034] UV nanoimprinting technology reduces microstructure processing time from 6-8 hours to 30 seconds, and eliminates the need for a mask (reducing costs by 50%). Within a pressure range of 3-8MPa, the microstructure can be fully formed. If the pressure is lower than this range, the resin will not be fully filled and the microstructure will be incomplete. If the pressure is higher than this range, microcracks will appear on the glass substrate (breakage rate >5%). Temperatures of 150-200°C can reduce the risk of glass deformation. Below this temperature range, the resin will have poor fluidity and reduced pattern replication accuracy. Above this temperature range, the glass will soften and deform. At 40-60mW / cm 2 The UV intensity can effectively control the curing rate. If it is lower than the UV intensity range, the curing time will be extended (>60s) and the production capacity will be reduced. If it is higher than the UV intensity range, it will cause local overheating and lead to resin shrinkage and cracking.
[0035] S3. Preparation of embedded conductive-insulating composite layer: silver nanowire grid with line width ≤ 20μm is deposited on the substrate surface by inkjet printing, followed by vacuum injection of silica aerogel precursor, and heating and curing at 80-100℃ to form an aerogel filling layer.
[0036] Inkjet-printed silver nanowires reduce precious metal usage by 70%, and aerogel filling achieves synergistic conductivity and thermal insulation, resolving the high thermal conductivity contradiction of traditional ITO. Silver nanowires with a line width of ≤20μm maintain a balance between transmittance and conductivity. If the line width exceeds this range, a visible grid will appear, resulting in a decrease in transmittance. The aerogel structure can be optimized at a curing temperature of 80-100°C to ensure effective aerogel curing. Below this curing temperature range, the precursor will not be completely hydrolyzed (porosity <85%); above this curing temperature range, the aerogel will become brittle (compressive strength <20kPa).
[0037] S4. Multifunctional composite coating: immerse the substrate in SiO2-TiO2-ZnO sol at a pulling speed of 1-3 mm / s, and form a ternary nano-composite coating layer by ultraviolet curing. The molar ratio of SiO2, TiO2, and ZnO in the sol is (5-7): (2-4): 1.
[0038] This one-step process simultaneously achieves anti-reflection, super-hydrophobicity, and antibacterial properties, reducing the process from 3-4 steps to 1 and shortening the production cycle by 40%. At a pulling speed of 1-3 mm / s, film thickness uniformity can be effectively controlled. Speeds below this range result in excessive film thickness (>200 nm) and internal stress cracking. Speeds above this range result in insufficient film thickness (<50 nm) and functional failure.
[0039] S5, lamination and strengthening, laminating the coated substrate and another glass substrate with the EVA film, placing them in an autoclave at a pressure of 1.0-1.5 MPa and a temperature of 120-140° C. for 0.5-1.5 hours.
[0040] EVA film exhibits optimal fluidity at temperatures between 120°C and 140°C, achieving a bubble rate of <0.1% when bonded to a honeycomb microstructure (>2% for PVB). Air bubbles in the EVA film can be effectively eliminated at a pressure of 1.0-1.5 MPa. Pressures below this range result in residual bubbles, while those above this range can cause the glass microstructure to collapse. EVA film fully crosslinks at temperatures between 120°C and 140°C. Temperatures below this range result in insufficient adhesion (peel force <10 N / cm), while those above this range can cause yellowing (transmittance decreases >5%). A treatment time of 0.5-1.5 hours ensures complete curing of the EVA film. Temperatures below this range result in incomplete curing and reduced durability, while those above this range increase energy consumption by 30%, reducing cost-effectiveness.
[0041] In this embodiment, the mold of the UV nanoimprint technology in step S2 is a nickel-based honeycomb structure template, the surface of which is coated with a release agent, which is a perfluoropolyether compound.
[0042] The nickel-based honeycomb structure template features high hardness, high temperature resistance, and a durability of 100,000 cycles. Its low mold cost reduces replacement costs. Perfluoropolyether (PFPE) has low surface energy and a release force of <0.1N / cm² (compared to >0.5N / cm² for traditional silicone release agents), effectively reducing the risk of microstructure tearing (breakage rate <0.1%). Furthermore, PFPE is UV-resistant and resistant to release agent residue contamination.
[0043] In this embodiment, the deposition accuracy of the silver nanowire grid in step S3 is ±2 μm, and the aerogel precursor is methyltrimethoxysilane hydrolyzate.
[0044] Silver nanowire widths are ≤20μm, and a ±2μm precision ensures grid spacing fluctuations of <10%. Methyl groups (-CH3) enhance the aerogel's hydrophobicity (contact angle >120°), preventing water absorption and the resulting degradation of thermal insulation properties.
[0045] In this embodiment, the UV curing conditions in step S4 are: wavelength 365nm, intensity 50-80mW / cm 2 , time is 5 to 15 minutes.
[0046] A wavelength of 365nm precisely matches the absorption peak of photoinitiators (such as Irgacure 184) in the sol, improving curing efficiency by 30%. At UV intensities of 50-80mW / cm², a balance between curing rate and thermal damage is achieved. Intensities below this range result in curing times exceeding 20 minutes, reducing production capacity. Intensities above this range can lead to localized temperatures exceeding 100°C and cracking of the coating (crack density >10 / cm²). A curing time of 5-15 minutes ensures complete crosslinking. Below this range, crosslinking levels fall below 70%, resulting in poor wear resistance. Curing times above this range increase energy consumption by 40% and can cause yellowing of the coating.
[0047] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A high-strength multifunctional glass panel, characterized in that: It includes a high-alumina silicate glass substrate, a surface composite functional layer, and an embedded conductive-thermal insulation composite layer; The Al2O3 content in the high aluminosilicate glass substrate is 15-20wt%, and the thickness of the high aluminosilicate glass substrate is 2-6mm; The surface composite functional layer includes a microstructure layer and a SiO2-TiO2-ZnO ternary nanocomposite coating layer from the inside to the outside, wherein the microstructure layer has a honeycomb structure, the inner wall of the microstructure layer is covered with a hydrophobic coating, and the thickness of the SiO2-TiO2-ZnO ternary nanocomposite coating layer is 50-200 nm; The embedded conductive-thermal insulation composite layer is located inside the high-alumina silicate glass substrate. The embedded conductive-thermal insulation composite layer is composed of a silver nanowire grid and silica aerogel filling the grid gaps. The silver nanowire grid is composed of a plurality of silver nanowires. The silver nanowire width is ≤20μm, and the grid spacing of the silver nanowire grid is 1-3mm.
2. The high-strength multifunctional glass panel according to claim 1, characterized in that: The hydrophobic coating of the microstructure layer is a fluorosilane compound, and the thickness of the microstructure layer is 10-30 nm.
3. The high-strength multifunctional glass panel according to claim 1, characterized in that: The molar ratio of SiO2, TiO2 and ZnO in the SiO2-TiO2-ZnO ternary nanocomposite coating layer is (5-7): (2-4):
1.
4. The high-strength multifunctional glass panel according to claim 1, characterized in that: The silica aerogel has a pore size of 10-50 nm and a density of 0.05-0.15 g / cm 3 .
5. A process for processing a high-strength multifunctional glass panel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, substrate forming and pretreatment, using a float process to prepare a high-alumina silicate glass substrate with an Al2O3 content of 15-20wt%, and then plasma cleaning after cutting; S2. Microstructure processing: Using UV nanoimprint technology, a honeycomb microstructure with a unit size of 10-50 μm and a depth of 5-20 μm is imprinted on the substrate surface. The imprinting conditions are: pressure 3-8 MPa, temperature 150-200 ° C, UV curing wavelength 365 nm, intensity 40-60 mW / cm 2 ; S3, preparation of embedded conductive-insulating composite layer, depositing silver nanowire grid with line width ≤ 20μm on the substrate surface by inkjet printing, followed by vacuum injection of silica aerogel precursor, and heating and curing at 80-100℃ to form aerogel filling layer; S4, multifunctional composite coating, immersing the substrate in SiO2-TiO2-ZnO sol at a pulling speed of 1-3 mm / s, and forming a ternary nanocomposite coating layer by ultraviolet curing, wherein the molar ratio of SiO2, TiO2, and ZnO in the sol is (5-7): (2-4): 1; S5, lamination and strengthening, laminating the coated substrate and another glass substrate with the EVA film, placing them in an autoclave at a pressure of 1.0-1.5 MPa and a temperature of 120-140° C. for 0.5-1.5 hours.
6. The processing technology of a high-strength multifunctional glass panel according to claim 5, characterized in that: The mold of the ultraviolet nanoimprinting technology in step S2 is a nickel-based honeycomb structure template, the surface of which is coated with a release agent, which is a perfluoropolyether compound.
7. The processing technology of a high-strength multifunctional glass panel according to claim 5, characterized in that: The deposition accuracy of the silver nanowire grid in step S3 is ±2 μm, and the aerogel precursor is methyltrimethoxysilane hydrolyzate.
8. The processing technology of a high-strength multifunctional glass panel according to claim 5, characterized in that: The UV curing conditions in step S4 are: wavelength 365nm, intensity 50-80mW / cm 2 , time is 5 to 15 minutes.
Citation Information
Cited By
High-strength and high-flatness glass substrate for chip packaging and preparation method of high-strength and high-flatness glass substrate
CN121666097A
High-strength high-flatness glass substrate for chip packaging and method of manufacturing the same
CN121666097B
